Effect of angiotensin II on irradiation exacerbated decompression sickness - Jie-Fu Fan; Yang-Kai Wang; Min Liu; Guang-Sheng Liu; Tian-Jiao Min; Rui-Yong Chen; Ying He (Scientific Reports, 2023)
Abstract In some complicated situations, decompression sickness (DCS) combined with other injuries, such as irradiation, will seriously endanger life safety. However, it is still unclear whether irradiation will increase the incidence of DCS. This study was designed to investigate the damage effects of irradiation on decompression injury and the underlying mechanism. Sprague–Dawley rats were exposed to irradiation followed by hyperbaric decompressing and the mortality and decompression symptoms were observed. Lung tissue and bronchoalveolar lavage fluid were collected to detect the lung lesion, inflammation response, activity of the angiotensin system, oxidative stress, and relative signal pathway by multiple methods, including Q-PCR, western blot, and ELISA. As a result, pre-exposure to radiation significantly exacerbated disease outcomes and lung lesions of DCS. Mechanically, the up-regulation of angiotensin-converting enzyme expression and angiotensin II levels was responsible for the exacerbated DCS and lung lesions caused by predisposing irradiation exposure. Oxidative stress and PI3K/AKT signal pathway activation in pulmonary tissue were enhanced after irradiation plus decompression treatment. In conclusion, our results suggested that irradiation could exacerbate lung injury and the outcomes of DCS by activating the angiotensin system, which included eliciting oxidative stress and activation of the PI3K/AKT signal pathway.